HUBUNGAN SENAM HAMIL DENGAN TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN - Tinta Julianawati (Universitas Pahlawan Tuanku Tambusai, 2022)
The prevalence of anxiety symptoms in first trimester pregnant women is 7.9%, second trimester is 8% and third trimester is 8.8%. Uncontrolled anxiety can have an impact not only on the condition of the mother but also on the condition of the fetus. Pregnant women with healthy bodies can carry out routine daily tasks and reduce anxiety before the birth process. The way that can be done to keep the body fit and healthy is by doing pregnancy exercises. The purpose of this study was to analyze the relationship between pregnancy exercise and the anxiety level of third trimester pregnant women in facing labor. This research is an observational analytic study with a cross sectional design. The population was 33 third trimester pregnant women with a gestational age of 36 weeks. Samples were taken by simple random sampling technique and a sample of 31 research subjects was obtained. The research was conducted from 17 August to 25 September 2022. Data collection used a questionnaire to determine pregnancy exercise and determine anxiety levels. The results showed that 45.2% of respondents did not do pregnancy exercise, 38.7% of respondents felt very heavy anxiety. Data were analyzed using Spearman's rank analysis. The results of calculations with the Spearman test obtained ρcount -0.3888 and compared with the ρtable value of 0.3560 so that ρcount> ρtable. The results of this study indicate that there is a significant relationship between pregnancy exercise and the level of anxiety of third trimester pregnant women in facing labor. Keywords: Pregnancy exercise, Anxiety, Pregnant women of trimester III, Childbirth